Funding medical education: should we follow a different model to general higher education? - Kieran Walsh (Istituto Superiore di Sanità, 2015)
ISSUE. There has been much recent discussion on the funding of medical education. There has also been much discussion about the funding of higher education more generally. EVIDENCE. The topics of discussion have included the rising costs of education; who should pay; the various potential models of funding; and how best to ensure maximum returns from investment. IMPLICATIONS. Medical education has largely followed the emerging models of funding for higher education. However there are important reasons why the funding models for higher education may not suit medical education. These reasons include the fact that medical education is as important to the public as it is to the learner; the range of funding sources available to medical schools; the strict regulation of medical education; and the fact that the privatisation and commercialisation of higher education may not been in keeping with the social goals of medical schools and the agenda of diversification within the medical student population.